2014
DOI: 10.1104/pp.114.236539
|View full text |Cite
|
Sign up to set email alerts
|

Plants Utilize a Highly Conserved System for Repair of NADH and NADPH Hydrates    

Abstract: NADH and NADPH undergo spontaneous and enzymatic reactions that produce R and S forms of NAD(P)H hydrates [NAD(P)HX], which are not electron donors and inhibit various dehydrogenases. In bacteria, yeast (Saccharomyces cerevisiae), and mammals, these hydrates are repaired by the tandem action of an ADP-or ATP-dependent dehydratase that converts (S)-NAD(P)HX to NAD(P)H and an epimerase that facilitates interconversion of the R and S forms. Plants have homologs of both enzymes, the epimerase homolog being fused t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
68
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(83 citation statements)
references
References 50 publications
12
68
2
Order By: Relevance
“…The dehydratase and epimerase activities of NNRD and NNRE, respectively, were also performed and validated with NADPH, leading to very similar results (data not shown). These data are corroborated by an independent study that appeared while this manuscript was under review (24).…”
Section: Identification Of the Genes Involved In The Nad(p)hx Repairsupporting
confidence: 83%
“…The dehydratase and epimerase activities of NNRD and NNRE, respectively, were also performed and validated with NADPH, leading to very similar results (data not shown). These data are corroborated by an independent study that appeared while this manuscript was under review (24).…”
Section: Identification Of the Genes Involved In The Nad(p)hx Repairsupporting
confidence: 83%
“…However, no or extremely low levels of protein could be detected in either mutant line by immunochemical analysis using an antibody specifically raised against Arabidopsis PDX3 ( Figure 2C). By contrast, a strong protein band of ;55 kD could be detected in wild-type protein extracts consistent with the expected molecular mass of mature PDX3 (52.2 kD) (Colinas et al, 2014;Niehaus et al, 2014). Therefore, these two lines can be considered as strong pdx3 mutants.…”
Section: Pdx3 Is Required For Plant Vegetative Growth and Developmentmentioning
confidence: 74%
“…In the salvage pathways of the plant model Arabidopsis thaliana, PN, PM, and PL can be phosphorylated by a kinase (named SALT OVERLY SENSITIVE4 [SOS4]; , and the phosphorylated forms, PNP and PMP, can be converted into PLP by the action of the oxidase PDX3 (González et al, 2007;Sang et al, 2007Sang et al, , 2011 (Figure 1). Interestingly, the PDX3 enzyme consists of two domains; the PMP/PNP oxidase domain is located at the C terminus and is fused to an N-terminal epimerase that has recently been implicated in nicotinamide nucleotide repair (annotated NNRE) (Marbaix et al, 2011;Colinas et al, 2014;Niehaus et al, 2014). In addition, a pyridoxal reductase converting PL into PN, found originally in yeast (Morita et al, 2004), has more recently been characterized in Arabidopsis (Herrero et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a proteomic study (Ito et al, 2011) found the At5g32470 protein in a cytosolic fraction. Prompted by this latter finding, we discovered that At5g32470 and all of the orthologous sequences examined include a methionine residue near the end of the targeting peptide (residue 47 in At5g32470) that could potentially serve as an alternative translation start site (Supplemental Figure 6), as reported for other plant proteins (Daras et al, 2014;Niehaus et al, 2014;Bohrer et al, 2015;Ellens et al, 2015). If used, this second translation start site would eliminate the putative mitochondrial targeting peptide.…”
Section: The At5g32470 Protein Localizes To the Cytosol And Potentialmentioning
confidence: 81%